Multiple Roles of MYC in Integrating Regulatory Networks of Pluripotent Stem Cells - Fagnocchi, Luca; Zippo, Alessio (Frontiers in Cell and Developmental Biology, 2017)
Pluripotent stem cells (PSCs) are defined by their self-renewal potential, which permits their unlimited propagation, and their pluripotency, being able to generate cell of the three embryonic lineages. These properties render PSCs a valuable tool for both basic and medical research. To induce and stabilize the pluripotent state, complex circuitries involving signaling pathways, transcription regulators and epigenetic mechanisms converge on a core transcriptional regulatory network of PSCs, thus determining their cell identity. Among the transcription factors, MYC represents a central hub, which modulates and integrates multiple mechanisms involved both in the maintenance of pluripotency and in cell reprogramming. Indeed, it instructs the PSC-specific cell cycle, metabolism and epigenetic landscape, contributes to limit exit from pluripotency and modulates signaling cascades affecting the PSC identity. Moreover, MYC extends its regulation on pluripotency by controlling PSC-specific non-coding RNAs. In this report, we review the MYC-controlled networks, which support the pluripotent state and discuss how their perturbation could affect cell identity. We further discuss recent finding demonstrating a central role of MYC in triggering epigenetic memory in PSCs, which depends on the establishment of a WNT-centered self-reinforcing circuit. Finally, we comment on the therapeutic implications of the role of MYC in affecting PSCs. Indeed, PSCs are used for both disease and cancer modeling and to derive cells for regenerative medicine. For these reasons, unraveling the MYC-mediated mechanism in those cells is fundamental to exploit their full potential and to identify therapeutic targets.